6-Axis Gesture Controlled Smart Robot - S S Naga Pavan Kumar T, K. Kishore, Dayanand Kalapala (International Journal of Advanced Science and Technology, 2020)
Electromechanical machines are significant for the present-day world, do thing’s quicker, and gives the best execution in basic circumstances. The structure of 6 hubs signal-controlled robot is planned which moves around in four unique ways which incorporate a few segments like gripper to pick and spot usefulness. This paper presents that human need a security tip at basic Work areas. A few models incorporate such kinds of conditions are managing perilous concoction analysis, chimneys, COVID-19 disengagement ward places, and some more. These sorts of assignments are worked by an easy to understand gadget like advanced cells which can control the movement of the vehicle just as it’s automated arm. This gadget comprises a Bluetooth module as a receptor for the vehicle. This model planned to send API orders to the microcontroller which acts as per the program written in it.